DAYA DUKUNG LINGKUNGAN FISIK TERHADAP KELAYAKAN DAYA TARIK WISATA TAMAN TIRTA GANGGA DESA ABABI KABUPATEN KARANGASEM - Sukmana, Bayu Dwitya; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 4 No 1 (2016): VOL 4, NO 1 (2016): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2016.v04.i01.p02, 2016)
ABSTRACT The development of tourism in essence to develop and utilize the destination and tourist attraction in the form of a beautiful natural resources , the diversity of flora and fauna , cultural, historical, archaeological objects and cultural diversity . In order to achieve the objectives of tourism development of the Development of tourism should be directed to the use of natural resources , the greater the resources you have, the greater the hope for achieving development goals and the development of tourism . Based on studies that revealed the problems , how the carrying capacity of the physical environment on the feasibility of tourism attraction tirta gangga, Karangasem regency Ababi village? To unravel this issue, this study uses primary and secondary data sources , whereas the type of data used is also quantitative and qualitative data . Methods of collecting data through observation , interviews , and literary study . Analysis of the data used is a qualitative descriptive analysis. The results showed that , tourism development in the tourist destination , has an influence on the physical environment . In terms of its physical environment , support the building in a popular tourist destination such as supporting the existence of a tourist destination has been organized than previous years .
Keywords: Carrying Capacity, Physical Environment, Social and Cultural Environment, Tourism, Eligibility.